The evolution of publication hotspots in the field of telemedicine from 1962 to 2015 and differences among six countries. (April 2018) - Wang, Yanjun; Zhao, Ye; Zheng, Jianzhong; Zhang, Ailian; Dong, Haiyuan
Introduction: Telemedicine has been implemented in many countries and has captured the attention of many researchers. Herein, we aim to quantify publication hotspots in the field of telemedicine, analyse their evolution, compare them in different countries, and provide visual representations. Methods: We used software tools to process PubMed entries for a 54-year period and identified publication hotspots using keyword frequency analysis. We employed a keyword co-occurrence analysis, principal component analysis, multidimensional scaling analysis, and network visualization technology. Results: The number of Medical Subject Heading (MeSH) terms increased with time. The most common subcategories of telemedicine between 1962 and 2015 were Remote Consultation, Teleradiology, and Telepathology. The most popular information communication technologies in telemedicine publications were related to the Internet and cell phones. The topics of Patient Satisfaction, Treatment Outcomes, and Home Care Services associated with telemedicine were highlighted after the 1990s. Use frequency of the terms Cell Phones and Self-Care increased drastically in the past six years, and the publication focus in six countries that had the highest output was different. Knowledge network maps and perceptual maps show the relationship between high-frequency MeSH terms. Discussion: The telemedicine field has experienced significant growth and expansion in knowledge and innovation in the last 54 years. Publication hotspots for telemedicine lean towards clinical treatment, home care services, and personal care, and countries emphasize publishing in areas related to their national characteristics. This study quantitatively discusses publication hotspots, provides an objective and systematic understanding of this field, and suggests directions for future telemedicine research.